ONLINE PARAMETERS ESTIMATION OF TIME-DELAYED DYNAMICS OF PROCESSES FOR INDUSTRIAL USE - Ghorai, Prasenjit (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This article presents an online identification scheme for modeling time-delayed processes using a simple setpoint-weighted relay autotuning approach for industrial use. Four sets of mathematical expressions are prescribed for the identification of process dynamics using the limit cycle information in terms of two second-order plus time delay and two first-order plus time delay models. The model parameters are directly identified from the explicit expressions derived based on setpoint weighted relay gain, proportional-integral-derivative (PID) controller parameters, and closed-loop marginal criteria. An experimental setup of a single-input-single-output (SISO) liquid level control system is considered to validate the proposed identification scheme. Two first-order plus time delay transfer functions are identified from the proposed online method for the considered system and compared with a model obtained from an offline method.